SOSIABILITAS PARA NETTER DI INDONESIA: KASKUSER REGIONAL YOGYAKARTA - Weni Arindawati (Jurnal Politikom Indonesiana, 2016)
AbstractThis is a study on the  sociability  of  netters  as  reflected in the phenomenon of virtual community or online groups. This study attempts to investigate how the sociability of netters, KASKUS community of Yogyakarta  Region,  is  shaped  in  cyberspace.  As  a  result,  this  study  is  aimed  at  understanding  and explaining  the  sociability  built  by  the  netters.  Besides,  this  study  is  aimed  at  describing  the communication, consolidation, and confirmation of the netters.  And  ,  it is also aimed at pointing out the  dissimilarity  or  similarity of  online and offline  sociability.  In virtual ethnographic research, theinteraction  of  virtual  communities  can  actually  be  assessed  based  on  its  Computer-mediated Communication (CMC)  practices.  Therefore, observations are conducted by the researcher to  explorethe experience and self-reflection of both the researcher herself and informants. As a consequence, this study  can  be  classified  into  a  qualitative  research  involving  a  combination  of  ethnographic observation, interviews, and group discussions. Key words: virtual community; sociability; CMC; KASKUS